2021
DOI: 10.18295/squmj.2021.21.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Outcomes of Gastrointestinal Stromal Tumours in Oman

Abstract: Objectives: This study aimed to report the clinicopathological features, management and long-term outcomes of patients with gastrointestinal stromal tumours (GISTs) in Oman. Methods: This retrospective study was conducted on patients treated for GIST between January 2003 and December 2017 at three tertiary referral centres in Muscat, Oman. All patients with confirmed histopathological diagnoses of GIST and followed-up at the centres during this period were included. Relevant information was retrieved from hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Similarly, females were more likely to have benign GIST tumors as compared to malignant GIST tumors. Al-Maqrashi et al in their study found the majority of the patients to be female (56.8%) [12]. The most common area of the tumor was the stomach (63.6%) and then the ileum/jejunum (18.2%).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, females were more likely to have benign GIST tumors as compared to malignant GIST tumors. Al-Maqrashi et al in their study found the majority of the patients to be female (56.8%) [12]. The most common area of the tumor was the stomach (63.6%) and then the ileum/jejunum (18.2%).…”
Section: Discussionmentioning
confidence: 91%